A randomized crossover trial with experience sampling to test placebo effects on pathological skin-picking - Anne Schienle; Sara Kohlhofer; Johannes Wilhelm; Sandra Tanzmeister (Scientific Reports)
Abstract Emotional distress is a typical trigger for pathological skin-picking (PSP). Given that placebo treatments can reduce emotional distress, the present study sought to investigate placebo responsiveness in individuals with PSP. In this randomized crossover trial, 69 participants (90% female, M = 31 years) with self-reported PSP underwent two weeks with daily placebo treatment (pills introduced as ‘N-acetylcysteine’ to reduce skin-picking) and two weeks without placebo treatment. Participants used a smartphone application to provide daily ratings for their skin-picking symptoms, as well as their stress levels. Questionnaires assessing the severity of skin-picking, stress, and difficulties in emotion regulation were completed before and after the two-week intervals (with and without the placebo). Questionnaire data indicated that placebo treatment reduced skin-picking severity (large effect) as well as perceived stress and difficulties in emotion regulation (medium effects). App-based assessments revealed that the placebo effect was limited to a moderate reduction in the urge to engage in skin-picking behavior, observed only during the second week of treatment, with no significant impact on daily stress levels. Individuals with PSP are responsive to placebo treatment. However, the magnitude of the placebo effect appears to be overestimated when relying on retrospective questionnaire data compared to ecological momentary assessments.